Research progress of access control model and policy in online social networks - Tian-zhu CHEN; Yun-chuan GUO; Ben NIU; Feng-hua LI (网络与信息安全学报)
As one of the effective approach to protecting information,access control which makes the information only accessed by legitimate users and prevents information leakage,has been widely used in online social networks.The characteristics of OSN were analyzed.From two angles of access control model and access control strategy,the research of access control in online social networks were discussed deeply,the related research was counted and analyzed.